1996
DOI: 10.1021/bi952616k
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Modification of Interleukin-2 by the Combined Use of Genetic Engineering Techniques and Transglutaminase

Abstract: Exploring a new method for the site-specific incorporation of functional groups into proteins, we have studied the combined use of genetic engineering techniques and enzymatic methods. Specifically, a short peptide for use as a substrate of guinea pig liver transglutaminase (TGase) is introduced at the N terminus of human interleukin-2 (hIL-2). The expressed chimeric protein (rTG1-IL-2) is chemically modified at a glutamine site in the appended sequence by TGase-catalyzed transamination with two amines, monoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…Several groups, including ours, have previously demonstrated that this enzymatic reaction can be exploited for a variety of applications in drug delivery and tissue engineering. For example, research groups have reported on the transglutaminase-catalyzed site-specific modification of proteins with PEG (PEGylation) [17,18], the cross-linking of PEG [19,20] or proteins such as collagen [21] or gelatin [22] into hydrogel networks, and also the specific covalent immobilization of exogenous bioactive ligands into fibrin networks to change its biomolecular characteristics and create celland tissue-specific microenvironments [23,24]. In the latter case, the release of covalently bound biomolecules is coupled to the proteolytic degradation of the fibrin gel associated with invading cells during remodeling processes, making this matrix platform attractive for diverse tissue regeneration applications [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups, including ours, have previously demonstrated that this enzymatic reaction can be exploited for a variety of applications in drug delivery and tissue engineering. For example, research groups have reported on the transglutaminase-catalyzed site-specific modification of proteins with PEG (PEGylation) [17,18], the cross-linking of PEG [19,20] or proteins such as collagen [21] or gelatin [22] into hydrogel networks, and also the specific covalent immobilization of exogenous bioactive ligands into fibrin networks to change its biomolecular characteristics and create celland tissue-specific microenvironments [23,24]. In the latter case, the release of covalently bound biomolecules is coupled to the proteolytic degradation of the fibrin gel associated with invading cells during remodeling processes, making this matrix platform attractive for diverse tissue regeneration applications [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous approaches have been explored to deal with the problem of biological activity losses as a result of PEGylation: sitespecific PEGylation, sometimes in combination with site-specific mutagenesis (Goodson and Katre, 1990;Kinstler et al, 1996;Gaertner and Offord, 1996;Sato et al, 1996;Cazalis et al, 2004); protection of receptor-binding site during conjugation (Caliceti et al, 1993(Caliceti et al, , 1994; and reversible PEGylation (Peleg-Shulman et al, 2004;Zalipsky et al, 2007). Each of these approaches has its merits and potential effectiveness in specific situations, although all of them have nontrivial technical obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…gpTGase has been demonstrated in many cases to label various proteins fused with ‘Q-tag’, a 6- or 7-mer transglutaminase recognition sequence. Interleukin-2 and glutathione S -transferase have been attached with monodansyl cadaverine (Sato et al 1996) and fluorescein cadaverine (Taki et al 2004), respectively, by gpTGase. Lin and Ting (2006) demonstrated the labeling of Q-tagged proteins by gpTGase both in vitro and on the surface of living mammalian cells with biotin, fluorophores, and a benzophenone photoaffinity probe.…”
Section: Site-specific Conjugationmentioning
confidence: 99%